ANALISIS ISOLASI PADA GENERATOR PEMBANGKIT LISTRIK TENAGA AIR SAGULING - Anhar Fauzi Muhammad; Ulinnuha Latifa; Insani Abdi Bangsa (Politeknik Harapan Bersama Tegal, 2021)
Abstract - the system at the electric power plant has some main equipment that has high voltage, one of them is the generator. High voltage equipment has an isolation system that plays an important role in the main operation of a normal generator. many found the damage to electrical equipment is happening on the isolation system, therefore it needed periodically monitoring to maintain the quality of the isolation. one of the ways for monitoring is to check and detect the partial discharger at the isolation. partial discharger could exist because of the isolation of the electrical equipment getting a high electric field pressure. if an isolation run into partial discharger in a long period of time, that would result in malfunction or damage at the isolation. Isolation that used in generator at saguling hydroelectric power plant was E class that had maximum temperature of 120’c. If the generator temperature exceed 120’c that means isolation at the generator encounter a disturbance and that would endanger the generator, and the most danger of all is the generator may burnt. This research done at saguling hydroelectric power plant. With the examination using raytech imprared thermometer and it was done manually. This research purpose was to acknowledge actual condition of the generator isolation quality at the saguling hydroelectric power plant. The result of this research showed that isolation at the mentioned generator still proper to be used because of the temperature doesn’t exceed the limit that had been determined.